The effects of transglutaminase on the qualitative properties of different pastırma types - Kaban, Güzin; Kaya, Mükerrem; Hazar, Fatma Yagmur (Elsevier BV, 2021)
Abstract The aim of the study was to determine the effect of microbial transglutaminase enzyme (MTgase) on the volatile compound (VC) profile, free amino acid (FAA) composition, maximum cutting force and aw of pastirma types (sirt, kusgomu, sekerpare, kurek, and bohca). In addition, changes in pH, TBARS and instrumental color values during cold storage under MAP (70% N2 + 30% CO2) were examined for 6 months. Transglutaminase caused a decrease in the level of VCs. These treatment had a significant effect on FAA composition. VCs and FAA were affected by pastirma type factor. MTgase increased the maximum cutting force. The effect of transglutaminase on the pH was depends of pastirma types. Four pastirma types (sirt, kusgomu, kurek and bohca) without MTgase showed higher TBARS value than with MTgase. As storage time progressed, L* and a* values decreased depending on pastirma types. In all pastirma types pH ranged between 5.61 and 5.72 during cold storage under MAP condition.